From victims to experts: civic agency strategies for identifying missing people in Mexico - Ana Cepeda; Salvador Leetoy (Íconos)
This article analyzes different forms of civic agency and citizen science developed by the women of the “Amor por Ellxs” collective in the Guadalajara Metropolitan Zone, Mexico. Since 2016 these women have organized themselves in order to search for their missing relatives and to demand the adoption of a new “Missing Persons “Bill by the Jalisco State Legislature. First, the article discusses the involvement of the collective in the search for the victims and in the management of the resulting emotions. These expressions of agency allow the women to transcend their victimhood and to become collectively empowered. Next, their communications, -as displayed in their Facebook page-, are reviewed. Here we highlight their citizen science strategies for building extra-institutional knowledge. In this way- and together with other solidary social actors- the group is able to develop a more efficient search and identification of the missing persons. Cyberethnography, in- depth interviews and participant observation detect different kinds of actions, which include dissemination of search, localization and body identification file cards; recommendations on new protocols to be applied in cases of disappearance and emotional support to the families. The article concludes that pain, powerlessness and anger are channeled towards citizen science activities which open the doors for social empowerment in the face of the failure of responsible institutions to find the disappeared persons.